We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website.
Please click on "Accept cookies" if you agree to the setting of cookies. Cookies that do not require consent remain unaffected by this, see
cookie policy and privacy policy.
DECLINE COOKIES

#1**+2 **

Explicit rule :

a_{n} = a_{1} + d(n - 1)

Where a_{n} is the nth term ......a_{1} is the first term and d is the common difference [ here = - 6]

So we have

a_{n} = 12 + - 6(n - 1) = 12 - 6(n - 1)

CPhill Dec 14, 2018

#2**+1 **

For my multiple choice it has these as the choices.

an=18+6n

an=6−6n

an=18−12n

an=18−6n

awsometrunt14
Dec 14, 2018